2022
DOI: 10.1097/mop.0000000000001107
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial diarrhoea

Abstract: Purpose of reviewThis review describes recent findings about the burden of bacterial diarrhoea and its potential complications, newer diagnostics, the emerging threat of multidrug resistance, and the promise of vaccines in development.Recent findingsIntroduction of rotavirus vaccines in over 110 countries has changed the landscape of diarrheal pathogens. In upper middle and high-income countries, the incidence of rotavirus-specific and all-cause gastroenteritis has declined substantially, and norovirus has bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…STEC/VTEC causes a wide range of human gastrointestinal disorders, from watery and bloody diarrhea to hemorrhagic colitis. Infection can also result in the life-threatening hemolytic uremic syndrome (HUS), which is considered to be caused by Shiga toxins (Stx) [ 69 , 70 ]. It is demonstrated that heavy rainfall and high temperature are statistically significantly associated with the occurrence of waterborne VTEC outbreaks [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…STEC/VTEC causes a wide range of human gastrointestinal disorders, from watery and bloody diarrhea to hemorrhagic colitis. Infection can also result in the life-threatening hemolytic uremic syndrome (HUS), which is considered to be caused by Shiga toxins (Stx) [ 69 , 70 ]. It is demonstrated that heavy rainfall and high temperature are statistically significantly associated with the occurrence of waterborne VTEC outbreaks [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, Shigella disease, also known as bacillary dysentery, is caused by Shigella sonnei from food, which leads to bacterial spreading and invasion in the intestinal epithelia and results in diarrhea. 106 Considering that the S. sonnei O-antigen polysaccharide is effective in stimulating the production of protective antibodies, Tian et al have developed the O-antigen based OMV vaccine by expressing the O-antigen in recombinant Salmonella via the LPS synthesis pathway. 107 Inspired by this work, vaccines basing on polysaccharide antigen-loaded bacterial OMVs have received increasing attention.…”
Section: Review Materials Advancesmentioning
confidence: 99%
“…An important issue of Campylobacter spp. of public health concern is the emerging of antibiotic resistant strains especially multidrug-resistant strains [11] that poses a challenge to the treatment of infections in humans. Infections caused by antibiotic-resistant strains of Campylobacter are more di cult to treat [12] particularly concerning those related to high levels of resistance to cipro oxacin and tetracycline [13][14][15].…”
Section: Introductionmentioning
confidence: 99%